Sickle cell disease: a comparative perspective on global and national initiatives - Kumar, Alok; Bhattacharya, Sudip (Frontiers in Hematology, 2024)
Sickle cell disease (SCD) is a genetic disorder caused by mutations in the β-globin chain of hemoglobin, leading to abnormal red blood cells, severe pain, anemia, organ damage, and increased infection risk. Inherited in an autosomal recessive manner, it mainly affects regions with high malaria incidence, like sub-Saharan Africa, the Middle East, and the Indian subcontinent. Management includes blood transfusions, hydroxyurea, folic acid, iron chelators, and hematopoietic stem cell transplantation (HSCT), the only curative option but limited by donor compatibility. Comprehensive healthcare management (CHCM) emphasizes patient education, nutrition, prophylactic antibiotics, and early intervention to reduce morbidity and improve quality of life. SCD presents a significant global health burden, particularly in regions with limited healthcare access, contributing substantially to child mortality. In sub-Saharan Africa, India, and the Middle East, SCD is prevalent, with approximately 300,000 infants born annually with the condition. In the United States, about 100,000 individuals, predominantly African Americans, are affected. National initiatives, such as Nigeria’s National Sickle Cell Disease Control Program and India’s National Sickle Cell Anaemia Elimination Mission, aim to improve outcomes through early screening, public education, and enhanced healthcare access. Global efforts by the WHO, GSCDN, and SCDC focus on strategic policies, advocacy, and international collaboration to improve care and reduce mortality. Challenges in implementing SCD prevention programs include the need for extensive genetic screening, robust healthcare infrastructure, and overcoming cultural stigmas. Research funding disparities between the Global North and South further hinder advancements. Future research avenues include gene editing technologies, improving prenatal diagnosis, enhancing newborn screening, understanding genetic modifiers, developing new pharmacological agents, and optimizing stem cell transplants. Collaborative efforts among researchers, healthcare providers, policymakers, and patient advocacy groups are essential to translate research into practical applications, ensuring accessible, effective, and equitable advancements in SCD prevention and treatment.